Matrix-Isolation Study and Ab Initio Calculations of the Structure and Spectra of Hydroxyacetone - Sharma, Archna (2008)
The structure of hydroxyacetone (HA) isolated in an argon matrix (at 12 K) and in a neat solid phase (at 12−175 K) was characterized by using infrared (IR) spectroscopy. The interpretation of the experimental results was supported by high-level quantum chemical calculations, undertaken by using both ab initio (MP2) and density functional theory methods. A potential-energy surface scan, carried out at the MP2/6-311++G(d,p) level of theory, predicted four nonequivalent minima, Cc, Tt, Tg, and Ct, all of them doubly degenerate by symmetry. The energy barriers for conversion between most of the symmetrically related structures and also between some of the nonequivalent minima (e.g., Tg → Tt and Ct → Tt) are very small and stay below the zero-point vibrational level associated with the isomerization coordinate in the higher-energy form in each pair. Therefore, only Cc and Tt conformers have physical significance, with populations of 99 and 1%, respectively, in gas phase at room temperature. For the matrix-isolated compound, only the most stable Cc conformer was observed. On the other hand, the polarizable continuum model calculations indicated that in water solution, the population of Tt and Ct conformers might be high enough (ca. 6 and 11%, respectively) to enable their experimental detection, thus supporting the conclusions of a previous IR spectroscopy study [Spectrochim. Acta A 2005, 61, 477] in which the presence of more than one HA conformer in aqueous solution was postulated. The signatures of these minor conformers, however, do not appear in the spectra of the neat HA crystal, and the crystal structure was rationalized in terms of centrosymmetric hydrogen-bonded dimers consisting of two Cc-like units. Finally, we calculated 1H, 13C, and 17O NMR chemical shifts at different levels of theory and found them to agree with available experimental data.